Energy Efficient Mapping of Mixed Criticality Applications on Unrelated Heterogeneous Multicore Platforms - Awan, Ali (2016)
11th IEEE International Symposium on Industrial Embedded Systems (SIES 2016). 23 to 25, May, 2016. Krakow, Poland.